A-186 Preliminary Development of an Embedded Measure of Effort on the Memory Module of the Neuropsychological Assessment Battery (NAB). (30th August 2021) - Rodriguez, Alexandra; Carrillo, Alicia; Fasnacht-Hill, Lisa; Iwanicki, Sierra; Lechuga, David
Abstract: Objective: The Neuropsychological Assessment Battery (NAB) is an integrated neuropsychological battery for assessing cognitive skills in adults. The current study utilizes performance validity tests (PVTs) to interpret poor effort for scores on the NAB. Method: Sample consisted of 306 adult civil litigants referred for a neuropsychological evaluation aged 18 to 85 years with a mean age of 43 years. Education ranged from 8 to 20 years with a mean of 14 years of education. Poor effort was denoted by "failing" 2 or more PVTs versus individuals who did not fail any PVTs ("pass"). Results: Independent-samples t-tests were run to determine if there were differences in NAB Memory Module scores between the "pass" and "fail" groups. Multiple scores on NAB Memory Module yielded statistically significant differences. Scores were then used in subsequent ROC curve analyses to determine appropriate cutoff scores with an intent to maximally balance sensitivity and specificity. ROC curve analyses were favorable (i.e., AUC > 0.70) and yielded cut scores for List Learning A Immediate Recall (≤ 18), List Learning A Short Delayed Recall (≤ 6), List Learning A Long Delayed Recall (≤ 4), Shape Learning Immediate Recognition (≤ 15), Daily Living Memory Immediate Recall (≤ 39), Daily Living Memory Delayed Recall (≤ 11), List Learning A Discriminability (≤ 7), and Name/Address/Phone Delayed Recall (≤ 4) with sensitivity values ranging from 0.70 to 0.78 and specificity values ranging from 0.70 to 0.84. Conclusion: Results provide preliminary evidence of suggested cutoffs to identify suspected poor effort for various scores in the NAB Memory Module.